Automating container tracking system at Ahmedabad Container Depot - Verma, Sanjay, (SAGE Knowledge. Cases., 2015)
Ahmedabad Container Depot (ACD) was a fast growing inland container depot (ICD) in Ahmedabad. The area of the depot was 15 acres and it had a monthly turnover capacity of approximately 25,000 containers. The primary processes at the facility were imports, exports, and transshipments. ACD had been facing various challenges due to inefficient manual container tracking system at the facility. Due to good business, the company was able to reach 90-95% of its capacity which was also the main problem ACD had to deal with. The management wanted to increase efficiency by reducing the number of moves required to locate a container by implementing a technology solution. The Head IT of ACD, Bhavik, was examining proposals from vendors and had identified a few alternatives. He was also considering the options that other large container yards had used successfully. His dilemma was to determine the feasibility of the alternatives, particularly those which had not been tested by any other firms in the country. Also, implementing technology could cause a change in roles and responsibilities; dealing with that situation was another area of concern.